2002
DOI: 10.1128/jvi.76.20.10155-10168.2002
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Frequency of Cytotoxic T-Lymphocyte Responses: Identification of Immunodominant Regions of Human Immunodeficiency Virus Type 1 Subtype C

Abstract: (68), (iv) a high level of viral diversity (24,72,95), (v) preferential CCR5 coreceptor usage (1,19,78,92), and (vi) a number of unique subtype signatures across the viral genome (39,72,82,84).Vaccine protection against pathogenic simian immunodeficiency virus or simian-human immunodeficiency virus was demonstrated in a series of experiments with nonhuman primates (reviewed in references 6, 49, and 65). The induction of strong cytotoxic T-lymphocyte (CTL) responses that are able to control viral replication an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
91
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 92 publications
8
91
1
1
Order By: Relevance
“…As previously proposed [29], the absence of response may result from a deficit of Vpr peptide-specific naïve T cells in this donor in agreement with observations made in mice [33]. Previous studies showed that Vpr was targeted by CD8 1 T-cells [13][14][15] in a significant portion of seropositive donors [13][14][15]. CD8 1 T-cell epitopes were found to be spread all along the protein sequence [13,14].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As previously proposed [29], the absence of response may result from a deficit of Vpr peptide-specific naïve T cells in this donor in agreement with observations made in mice [33]. Previous studies showed that Vpr was targeted by CD8 1 T-cells [13][14][15] in a significant portion of seropositive donors [13][14][15]. CD8 1 T-cell epitopes were found to be spread all along the protein sequence [13,14].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies showed that Vpr was targeted by CD8 1 T-cells [13][14][15] in a significant portion of seropositive donors [13][14][15]. CD8 1 T-cell epitopes were found to be spread all along the protein sequence [13,14]. It is of note that the dominant HLA-A2-restricted T-cell epitope Vpr 59-67 [13] strongly overlaps with the Vpr 52-66 peptide we identified in this paper.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Initial reports included only subtype B-or C-infected patients (1,(47)(48)(49), but more recently other subtypes and CRF recombinant forms are being studied (18,22,27,28,35). On the other hand, the immunoprotective role of HIV-specific vaccine-induced T cells may be limited by the large genetic distance between viral strains circulating in different locations and the vaccine strain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the World Heath Organization and Centers for Disease Control recommend that Western blot confirmatory tests for HIV-1 infection must detect antibodies to p24 capsid protein among other viral proteins. Epitope mapping studies with HIV-1 have shown that p24 contains several cytotoxic T lymphocyte (CTL) epitopes that are important for immune control of HIV-1 infection (Johnson et al, 1991;Novitsky et al, 2002) and strong CTL responses have been shown to be necessary for successful vaccination in primates (Amara et al, 2001;Barouch et al, 2001;Shiver et al, 2002). Taken together, it is evident that p24 is an important antigen for controlling HIV-1 infection, it can be used in reliably and accurately diagnosing HIV infection, and more importantly, it can be included potentially in a preventive vaccine (Lefrere et al, 1992;Benson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%